The Glymphatic System in Diabetes-Induced Dementia - Kim, Young-Kook; Nam, Kwang Il; Song, Juhyun (Frontiers in Neurology, 2018)
The glymphatic system has been emerging as an important player in central nervous system diseases, by regulating vasculature impairment, effectively controlling the clearance of toxic peptides, modulating the activity of astrocytes, and being involved in the circulation of neurotransmitters in the brain. Recently, several studies indicated decreased activity of the glymphatic pathway under diabetes conditions including insulin resistance and hyperglycemia. Moreover, diabetes leads to the disruption of the blood brain barrier, decrease of apolipoprotein E expression, and secretion of norepinephrine in the brain, involving the impairment of the glymphatic pathway, and ultimately resulting in cognitive decline. Considering the increased prevalence of diabetes-induced dementia worldwide, the association between the glymphatic pathway and diabetes-induced dementia should be investigated and the mechanisms regarding their relationship should be discussed to promote the development of an effective therapeutic approach in the near future. Here, we review recent evidences about the association between glymphatic pathway dysfunction and diabetes conditions. We highlight that the enhancement of glymphatic system function during sleep may be beneficial toward the attenuation of neuropathology in diabetes-induced dementia. Moreover, we suggest that improving glymphatic system activity may be a potential therapeutic strategy for the prevention of diabetes-induced dementia.